The uses of psychoanalysis in law: the force of Jay Katz’s example - Burt, Robert A. (2016)
This article samples possible uses of psychoanalysis in law from the academic work of Joseph Goldstein and Jay Katz. Both start to recognize the importance of psychoanalysis to provide a serious and courageous attention to the non-rational dimensions of the human being, we should be aware in the world of law. Starting from this premise, the author explores two possible uses of psychoanalysis in law: one represented by Goldstein, focuses on using «psychoanalytic premises to resolve legal disputes», for example by providing psychoanalytic information to determine the best interests of the child in cases of custody, while the other, represented by Katz, who seeks to «create an awareness of conflict where all of the actors had previously been locked in a mutually reinforcing fantasy that no conflict existed», as it occurs in doctor-patient relationship, in order to rethink standards that had been set by law under an illusion of objectivity and rationality. The article explores these two approaches through examples, linking two perspectives adopted by Freud throughout his academic work and taking a preferred position by the position of Katz.